Virulence and pathogenicity of a Candida albicans mutant with reduced filamentation. (29th August 2019) - Peroumal, Doureradjou; Manohar, Kodavati; Patel, Shraddheya Kumar; Kumari, Premlata; Sahu, Satya Ranjan; Acharya, Narottam
Abstract: Deletion of DNA polymerase eta (Rad30/Polη) in pathogenic yeast Candida albicans is known to reduce filamentation induced by serum, ultraviolet, and cisplatin. Because nonfilamentous C. albicans is widely accepted as avirulent form, here we explored the virulence and pathogenicity of a rad30 Δ strain of C. albicans in cell‐based and animal systems. Flow cytometry of cocultured fungal and differentiated macrophage cells revealed that comparatively higher percentage of macrophages was associated with the wild‐type than rad30 Δ cells. In contrast, higher number of Polη‐deficient C. albicans adhered per macrophage membrane. Imaging flow cytometry showed that the wild‐type C. albicans developed hyphae after phagocytosis that caused necrotic death of macrophages to evade their clearance. Conversely, phagosomes kill the fungal cells as estimated by increased metacaspase activity in wild‐type C. albicans . Despite the morphological differences, both wild‐type and rad30 ∆ C. albicans were virulent with a varying degree of pathogenicity in mice models. Notably, mice with Th1 immunity were comparatively less susceptible to systemic fungal infection than Th2 type. Thus, our study clearly suggests that the modes of interaction of morphologically different C. albicans strains with the host immune cells are diverged, and host genetic background and several other attributing factors of the fungus could additionally determine their virulence.